PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica Juncea L) - Emilia S.A. Wangge; Maria Felmi Fowo (AGRICA, 2012)
This study aims at determining the optimum planting distance on the growth and yield of Bok Choy Sum plant, determining optimum planting distance of mustard greens plant that can optimize the growth and yield of Bok Choy Cum plant. This study employed group random design with single factor pattern including5 treatments, namelyPD0: Planting Distance 10 cm x 20 cm, PD1: Planting Distance 15 cm x 10 cm, PD2: Planting Distance 15 cm x 15 cm, PD3: Planting Distance 15 cm x 20 cm, PD4: Planting Distance 20 cm x 20 cm. All treatments were repeated four times so that there were 20 specimen garden-beds. The treatment of planting distance on Bok Choy has an impact on plant height, the width of leaves, but it did not have an impact on the number of leaves. The treatment of planting distance on result variable has a real impact on the variable of Bok Choy Sum-1 weight andBok Choy Sum weight ha-1. Planting distance 20 cm x 20 cm can optimize the growth and yield of Bok Choy Sum.